HOXD1 regulates neural crest cells differentiation and polycerate development in sheep - Cheng Zhang; Shuhong Zhang; Huifeng Xu; Guan Wang; Huan Zhang; Tenggang Di; Liming Tian; Menghan Chang; Fengyi Gao; Ming Li; Guangli Yang (Scientific Reports)
Abstract The polycerate trait in sheep is a complex phenotype regulated by polygenes. However, the mechanism behind multi-horned traits development and growth remains unclear. In this study, neural crest cells (NCCs) were isolated from mouse embryos, and the HOXD1 (Homeobox D1) gene was overexpressed in these cells to identify its function. Transcriptome analysis was performed to explore the key signaling pathway involved in forming the multi-horned traits in sheep. The results showed that the HOXD1 induced epithelial-to-mesenchymal transition (EMT) in mouse neural crest primary cells, affecting their migration but without significantly influencing proliferation. Furthermore, signaling pathway analysis suggested that HOXD1 may inhibit NCC proliferation by modulating Wnt rather than TGF-β signaling. Transcriptome analysis revealed that the HOXD1 gene affected the extracellular matrix of CXC family regulatory cells and promoted NCC differentiation. These findings provide a theoretical basis for further investigation into the regulation of multi-horned traits growth and development in sheep.